Ibuprofen vs. indomethacin for persistent ductus arteriosus closure in preterm infants - Deny Salverra Yosy; Ria Nova; Julniar M. Tasli; Theodorus Theodorus (Indonesian Pediatric Society, 2013)
Background Indomethacin and ibuprofen are anti-prostaglandinE2 agents administered for persistent ductus arteriosus (PDA)closure. Ibuprofen has weaker cyclooxygenase-1 inhibitor affinitythan that of indomethacin, causes decreased gastrointestinalcirculation, as well as brain and kidney side effects.Objective To compare the efficacy of oral ibuprofen andindomethacin for PDA closure in preterm infants.Methods A randomized double-blind controlled trial on preterminfants with PDA was performed in Moehammad HoesinHospital, Palembang, from October to December 2011. Persistentductus arteriosus was diagnosed by echocardiography. Subjectswere divided into two groups, and received either ibuprofen orindomethacin. Ibuprofen was given at a dose of 10 mg/kgBW /don day 1 and 5 mg/kgBW /d on days 2 and 3. Indomethacin wasgiven in three doses over 24 hour-intervals; the first dose was 0.2mg/kg, and the second and third doses were 0.1 mg/kg each.Results Sixty infants were enrolled in this study, 36 boys (60%)and 24 girls ( 40%). Fifty-two subjects completed the study protocol.Ductus arteriosus (DA) closure after treatment was observed in 22out of 26 subjects in the ibuprofen group and 19 out of 26 subjectsin the indomethacin group (P= 0.04). The mean DA diameterreductions after administration of ibuprofen or indomethacin were0.40 (SD 0.16) mm and 0.30 (SD 0.21) mm, respectively (95%CIof differences0.05 to0.17; P= 0.04). Serum creatinine was elevatedin the indomethacin group following treatment compared to theibuprofen group [P = 0.002, 95% CI of differences 0.06 to 0.27].Ductus arteriosus reopening occurred in 4 out of 19 subjects in theindomethacin group, while n one in the ibuprofen group .Conclusions Ibuprofen is better than indomethacin, in terms ofhigher PDA closure rate and mean DA diameter reduction aftertreatment. In additional, indomethacin has significantly greaterincrease in mean serum creatinine level after treatment thanibuprofen.